Miejsce gwary luzińskiej wśród gwar kaszubskich w świetle faktów fonetycznych i fonologicznych - Jocz, Lechosław (Slavia Occidentalis, 2016)
The article discusses the position of the Luzino dialect among Kashubian dialects in the light of phonetic and phonological features. The analysis takes into account eleven vowel features, one consonant feature and two prosodical features. A significant part of the discussed phenomena are the recent phenomena that have gone unnoticed, or been dealt with only marginally in the existing literature on the subject. One archaism links the Luzino dialect with the core central Kashubian area, but it is differentiated by seven innovations. The peripheral central Kashubian dialects indicate stronger relationships with the area of Luzino (one important archaism and one significant north Kashubian innovation). Three archaisms and nine innovations link the Luzino dialect with the north Kashubian area. Two vocal changes are typical only of the discussed area, and differentiate it from northern as well as southern Kashubian. From the phonetic and phonological point of view, the Luzino dialect should undoubtedly be classified as a marginal north Kashubian dialect.